(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This paper presents an integrated organisational-economic model for territorial water allocation in the Andijan region (10 districts), encompassing water limit-setting, compliance monitoring, and graduated economic liability for over-limit use. The model formulates a linear programming problem that jointly optimises water limits by linking sectoral demand (agriculture, industry, utilities), resource constraints, and economic efficiency indicators. Empirical estimation using 2020-2023 panel data for Andijan region demonstrates that the integrated model significantly outperforms purely organisational (+27%) or purely economic (+24%) approaches, reducing aggregate water losses by 49.4% and improving water use efficiency by 53.4%.